Climate Change in a Multinomial World. (1st September 2015) - Morgan, Robert F.
Abstract : "This is a new day, fresh and untouched. What will we do with it?" -Morning welcome, Native American Church. These days my own mornings do not begin untouched. They come with finger prints. On our planet's north and south hemispheres outside what we think of as the tropical zone, half the year is growing warmer in an accelerating manner. The other half of the year is marked with extreme changes: sometimes even colder with heavier snowfall. Climate change has put more moisture in the air, leading to a redistribution of water on a global scale. Millennial floods in some places, severe drought in others. Insect species should thrive under these new conditions while other species, note the current devastation in our oceans, may find the new conditions more than they can survive.